A method for preparing a three-dimensional structure electrode without a conductive agent and a binder
By constructing a three-dimensional active structure on copper foil, using gelatin and sodium alginate as C and N sources, a three-dimensional structural electrode without conductive agents and binders was prepared, which solved the problems of poor circulation stability and low conductivity of silicon negative electrode materials. Achieve efficient electrochemical performance improvement.
Patent Information
- Application Number
- CN202210837358.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-07-15
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2042-07-15
AI Technical Summary
The silicon negative electrode material has poor cycle stability and low conductivity during the cycle process. The preparation of existing silicon/carbon composite electrode materials has problems such as damage to active structure and uneven distribution of conductive agents.
A continuous and stable three-dimensional active structure was constructed on copper foil by one-step method, using gelatin and sodium alginate as C and N sources, and preparing three-dimensional structure electrodes without conductive agents and binders through ultrasonic dispersion, stirring, reaction and spraying. .
The cyclic stability and electrochemical performance optimization of silicon negative electrode materials during the in-depth deintercalation of lithium are achieved, and excellent cyclic performance and rate performance are achieved.
Smart Images

Figure CN115132972B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of silicon negative electrode materials, in particular to a method for preparing a three-dimensional structure electrode without a conductive agent and a binder. Background Art
[0002] Silicon anode is considered to be an ideal next-generation anode material due to its high theoretical specific capacity, suitable operating voltage, good safety, and environmental friendliness. However, its huge volume effect and low conductivity during the cycle process seriously hinder its further development.
[0003] In order to overcome the shortcomings of silicon negative electrode materials, compounding silicon with carbon materials with stable structure and excellent conductivity is an ideal and promising improvement method. Carbon materials can not only improve the poor conductivity of silicon materials, but also effectively exert their high capacity advantages. However, the preparation of existing silicon / carbon composite electrode materials still has some defects:
[0004] (1) During the high-temperature preparation and mechanical grinding of silicon / carbon composite materials, the design structure of the active material will be destroyed to a certain extent, resulting in silicon being directly exposed to the electrolyte;
[0005] (2) Generally, the additionally added conductive agent and binder do not have lithium insertion activity, which reduces the effective specific capacity of the electrode. At the same time, the uneven distribution of the conductive agent and binder will lead to problems such as poor electrochemical performance.
[0006] In addition, there is an existing technology that uses gelatin as a carbon source and silicon nanoparticles as active particles to synthesize a silicon-carbon composite material without a conductive agent or a binder. However, nano-silicon is more expensive than micron-sized silicon, and a single carbon coating is difficult to ensure the electrode stability of silicon during long-term cycles and higher rate requirements.
[0007] There is also an existing technology that uses Mexen as a conductive binder to prepare an independent electrode. However, the price of the finished Mexen is extremely expensive, which will greatly increase the production cost. If raw materials need to be purchased to prepare Mexen, highly corrosive acids such as hydrofluoric acid are required, which is very unfavorable for commercial production and environmental protection.
[0008] Therefore, seeking a simple and efficient method to design and synthesize a three-dimensional silicon-carbon composite electrode without a conductive agent and a binder is of great significance for the vigorous development of practical silicon-based negative electrode materials with high tap density and high energy density lithium-ion batteries. Summary of the invention
[0009] In order to overcome the shortcomings of the prior art, the present invention provides a method for preparing a three-dimensional structure electrode without a conductive agent and a binder, which solves the problem of poor cyclic stability of silicon in the deep lithium insertion and deinsertion process (phase change process). At the same time, green, environmentally friendly and low-cost gelatin and sodium alginate are selected as C and N sources, and a continuous and stable three-dimensional active structure is directly constructed on a copper foil by a one-step method. By optimizing the synthesis process, a three-dimensional structure electrode without a conductive agent and a binder is prepared.
[0010] The technical solution adopted by the present invention to solve the technical problem is: a method for preparing a three-dimensional structure electrode without a conductive agent and a binder, comprising the following steps:
[0011] S1: adding 0.01-0.1g of graphene oxide to 10-100ml of deionized water, and ultrasonically dispersing until the solution is clear; adding 0.05-0.2g of aluminum silicon alloy powder to the obtained clear solution, stirring evenly in a water bath at 25-35°C for 2-6 hours, then filtering and washing with water and anhydrous ethanol respectively, and vacuum drying to obtain product A;
[0012] S2 uses 0.5-4M hydrochloric acid to react with product A in a constant temperature water bath at 25-35°C for 12-28 hours, and washes with water and anhydrous ethanol for multiple times, and then vacuum-dries to obtain product B;
[0013] S3: 0.01-0.04 g of gelatin and 600-1200 μL of deionized water were stirred at 45-65° C. to form a uniform solution, which was recorded as solution A.
[0014] S4 Grind 0.02-0.06 g of product B and 0.01-0.04 g of sodium alginate in a mortar for 20-30 minutes until the powder particles are uniform, to obtain product C;
[0015] S5: mixing product C with solution A to form a uniform slurry, and coating the slurry on a copper foil to obtain product D;
[0016] S6: Pour the prepared Cu(NO3)2 solution into a nano spray bottle, spray it evenly on the surface of product D, and let it stand at room temperature for 10-30 minutes to allow it to be completely cross-linked to obtain product E.
[0017] S7 freeze-dries the product E and then calcines it to obtain the three-dimensional structure electrode.
[0018] Preferably, the weight content of silicon in the aluminum-silicon alloy powder in step S1 is 10-30%.
[0019] Preferably, the vacuum drying temperature in step S1 and step S2 is 60-90° C., and the drying time is 6-12 hours.
[0020] Preferably, in step S5, the sizing agent coating thickness on the aluminum foil is 200 μm.
[0021] Preferably, the mass concentration of the Cu(NO3)2 solution in step S6 is 1%-2%.
[0022] Preferably, the freeze-drying time in step S7 is 12-48 hours, and the process conditions of calcination are: calcination at 200-600° C. for 1-4 hours at a heating rate of 1-10° C. / min in a tubular furnace filled with argon.
[0023] Positive effects of the present invention: The present invention adopts a simple one-step method to prepare a pSi@rGO@NC / Cu three-dimensional structure electrode without a binder and a conductive agent, which has better electrochemical performance than the traditional pSi negative electrode. Among them, the three-dimensional carbon network derived from the composite of gelatin and sodium alginate cooperates with highly conductive reduced graphene oxide and copper element, and by maintaining the interface stability of the electrode structure and providing more mutually continuous electron / ion transport channels, the final three-dimensional structure electrode has excellent cycle performance and rate performance. The obtained pSi@rGO@NC / Cu electrode has a good electrochemical performance at 1Ag. -1 After 200 cycles, it can still maintain 1007.1mAh g -1 High reversible specific capacity; at 5Ag -1 Even at a high current density of 992.2 mAh g -1 In summary, the pSi@rGO@NC / Cu three-dimensional structure electrode without conductive agent and binder prepared by the method of the present invention overcomes some problems existing in traditional electrodes, effectively maintains the continuous and stable microstructure of the electrode material, and the carbon network derived from the composite of biomass gelatin and sodium alginate and the highly conductive metal Cu particles synergistically enhance the conductivity of the material.
[0024] The production of traditional electrodes requires grinding the active material first (which will destroy the microstructure of the material), then adding a certain amount of conductive agent and binder, and using a solvent to mix the three into a slurry and apply it on the surface of the copper foil. Therefore, in the preparation of traditional electrodes, the active structure will be destroyed and the conductive agent will be unevenly distributed, resulting in poor electrode cycle stability. In contrast, the three-dimensional structure electrode without conductive agent and binder in this patent directly coats the active material on the copper foil, and then directly calcines and carbonizes it, retaining the continuous three-dimensional structure on the surface of the copper foil without the need for grinding and adding conductive agent and binder like traditional electrodes. Therefore, the process of this patent is simple, and the structure of the electrode material is more completely retained, providing a new idea for the preparation of electrodes without conductive agent and binder. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1It is a schematic diagram of the process of preparing the three-dimensional structure electrode of the present invention;
[0026] Figure 2a is a SEM image of DJ-1 obtained in Example 1;
[0027] Figure 2b is another SEM image of DJ-1 obtained in Example 1;
[0028] Figure 3 are optical photographs of the DJ-1 obtained in Example 1 before and after folding;
[0029] Figure 4 The DJ-1 obtained in Example 1 at a current density of 1A -1 Long cycle performance under
[0030] Figure 5 The rate performance of DJ-1 at different current densities obtained in Example 1;
[0031] Figure 6a is the surface SEM image of DJ-1 obtained in Example 1 before cycling;
[0032] Figure 6b is the surface SEM image of DJ-1 obtained in Example 1 after 100 cycles;
[0033] Figure 6c This is a partially enlarged surface SEM image of DJ-1 obtained in Example 1 after 100 cycles;
[0034] Figure 6d is a cross-sectional SEM image of DJ-1 obtained in Example 1 before cycling;
[0035] Figure 6e is a cross-sectional SEM image of DJ-1 obtained in Example 1 after 100 cycles;
[0036] Figure 7 is the SEM image of DB-2 obtained in Comparative Example 2; DETAILED DESCRIPTION
[0037] The preferred embodiments of the present invention are described in detail below with reference to the accompanying drawings.
[0038] Reference Figure 1 The present invention provides a method for preparing a three-dimensional structure electrode without a conductive agent and a binder, comprising the following steps:
[0039] S1: adding 0.01-0.1g of graphene oxide to 10-100ml of deionized water, and ultrasonically dispersing until the solution is clear; adding 0.05-0.2g of aluminum silicon alloy powder (silicon weight content is 10-30%) to the obtained clear solution, stirring evenly in a water bath at 25-35°C for 2-6 hours, then filtering and washing with water three times and anhydrous ethanol three times respectively, and drying in a vacuum drying oven at 60-90°C for 6-12 hours to obtain product A;
[0040] Because the surface of the aluminum-silicon alloy microspheres has a positive charge, and the surface of the graphene oxide sheet has a negative charge, when Al obtains electrons during the stirring process, the two are electrostatically self-assembled to obtain product A in which graphene oxide is coated on the surface of the aluminum-silicon alloy microspheres;
[0041] S2 uses 0.5-4M hydrochloric acid to react with product A in a constant temperature water bath at 25-35°C for 12-28 hours, and washes with water and anhydrous ethanol three times respectively, and then puts into a vacuum drying oven at 60-90°C to dry for 6-12 hours to obtain product B;
[0042] The purpose of this step is to use hydrochloric acid to etch away the aluminum phase in the aluminum-silicon alloy microspheres to obtain a structure of graphene oxide-coated porous silicon microspheres.
[0043] S3: 0.01-0.04 g of gelatin and 600-1200 μL of deionized water were stirred at 45-65° C. to form a uniform solution, which was recorded as solution A.
[0044] S4 Grind 0.02-0.06 g of product B and 0.01-0.04 g of sodium alginate in a mortar for 20-30 minutes until the powder particles are uniform, to obtain product C;
[0045] S5: mixing product C with solution A to form a uniform slurry, and coating the slurry on a copper foil (the coating thickness is preferably 200 μm) to obtain product D;
[0046] S6: Pour the prepared Cu(NO3)2 solution with a mass concentration of 1%-2% into a nano spray bottle, spray it evenly on the surface of product D (the spraying amount is determined to be 2-6mL based on the amount of product B (0.02-0.06g), and let it stand at room temperature for 10-30 minutes to allow it to be completely cross-linked (spraying on the surface for cross-linking can form a complete and continuous three-dimensional active structure on the surface of the copper foil, which can better maintain the surface structure of the electrode during subsequent cycles, while the three-dimensional cross-linked structure obtained by existing common methods such as immersion is easily destroyed during the subsequent assembly process of traditional batteries, thereby resulting in a decrease in cycle stability), and obtain product E.
[0047] S7 freeze-dry the product E for 12-48 hours, and then calcine it at 200-600°C for 1-4 hours at a heating rate of 1-10°C / min in a tube furnace filled with argon to obtain the three-dimensional structure electrode (pSi@rGO@NC / Cu three-dimensional structure electrode).
[0048] In the above preparation process, the chain-like gelatin and sodium alginate are intertwined to form a composite network, and the oxygen-containing groups on the surface of graphene oxide will effectively self-assemble with the active sites on the composite network through electrostatic interaction and hydrogen bonding. 2+ The Na on the G unit of sodium alginate + Ion exchange will occur, causing the sodium alginate G units to cross-link to form a three-dimensional network structure, while the Al-Si derived pSi balls are wrapped inside the three-dimensional composite network. After high-temperature carbonization, the composite gel is transformed into a nitrogen-doped three-dimensional carbon cage, protecting the pSi inside it.
[0049] Example 1
[0050] This preferred embodiment 1 provides a method for preparing a three-dimensional structure electrode without a conductive agent and a binder, comprising the following steps:
[0051] S1: 0.05 g of graphene oxide was added to 50 ml of deionized water, and ultrasonic dispersion was performed until the solution was clear; 0.1 g of aluminum silicon alloy powder (silicon weight content was 20%) was added to the obtained clear solution, and the solution was stirred evenly in a water bath at 30° C. for 5 hours, and then filtered and washed with water and anhydrous ethanol respectively (washed with water three times and then washed with ethanol three times), and dried in a vacuum drying oven at 60-90° C. for 6-12 hours to obtain product A;
[0052] Because the surface of the aluminum-silicon alloy microsphere has a positive charge, and the surface of the graphene oxide sheet has a negative charge, the two are electrostatically self-assembled to obtain product A in which graphene oxide is coated on the surface of the aluminum-silicon alloy microsphere;
[0053] S2 reacts product A with 0.5M hydrochloric acid in a 30°C constant temperature water bath for 24 hours, and washes with water and anhydrous ethanol (washes with water three times and then with ethanol three times), and dries in a vacuum drying oven at 60-90°C for 6-12 hours to obtain product B;
[0054] S3: 0.02 g of gelatin and 1000 μL of deionized water were stirred at 55 °C to form a uniform solution, which was recorded as solution A.
[0055] S4: Grind 0.04 g of product B and 0.02 g of sodium alginate in a mortar for 20 minutes until the powder particles are uniform, to obtain product C;
[0056] S5: mixing product C with solution A to form a uniform slurry, and coating the slurry on a copper foil (coating thickness is 200 μm) to obtain product D;
[0057] S6 puts the prepared Cu(NO3)2 solution with a mass concentration of 2% into a nano spray bottle, sprays it evenly on the surface of product D (spraying volume is 4 mL), and lets it stand at room temperature for 15 minutes to completely cross-link it (spraying on the surface for cross-linking can form a complete and continuous three-dimensional active structure on the surface of the copper foil, which can better maintain the surface structure of the electrode during subsequent cycles, while the three-dimensional cross-linked structure obtained by existing common methods such as immersion is easily destroyed in the subsequent assembly process of traditional batteries, thereby resulting in a decrease in cycle stability), and obtains product E.
[0058] S7 freeze-dry the product E for 12-48 hours, and then calcine it at 450° C. for 2 hours in a tube furnace filled with argon at a heating rate of 2° C. / min to obtain the three-dimensional structure electrode, which is recorded as DJ-1.
[0059] Figure 2a and Figure 2b This is the SEM image of the DJ-1 three-dimensional structure electrode surface. It can be seen that the electrode surface presents a loose and porous structure, and the continuous chain network structure can be clearly observed.
[0060] Figure 3 These are optical photos of the DJ-1 three-dimensional structure electrode taken before and after folding. In the photos, it can be observed that there are no cracks and obvious active material shedding after the DJ-1 is folded, indicating that there is good adhesion between the active material and the copper foil.
[0061] like Figure 4 As shown in Figure 2, the DJ-1 3D electrode exhibits excellent long-term cycling performance with a first coulombic efficiency of 76.88% and a high charge / discharge rate at 1 A g -1 After 200 charge and discharge cycles, it still retains 1007.1mAh g -1 High reversible specific capacity.
[0062] Figure 5 It shows that when the current density is increased from 0.1A -1 Increase to 5Ag -1 The rate performance of DJ-1 three-dimensional electrode is excellent. -1 At such a high current density, the average capacity of the DJ-1 3D electrode is still as high as 768.8 mAh g -1 .
[0063] In order to further explore the structural changes of the electrode material before and after cycling, SEM images of the DJ-1 three-dimensional electrode before and after cycling were taken. Figure 6a , Figure 6b , Figure 6c The SEM images of the DJ-1 electrode before and after 100 cycles are shown. It can be observed that the DJ-1 electrode still maintains a relatively intact electrode structure after multiple charge and discharge cycles, indicating that the three-dimensional structure of the DJ-1 electrode itself plays a key role and effectively suppresses a series of negative problems caused by the volume effect of silicon materials. Cross-sectional view Figure 6d , Figure 6e This also proves the superiority of the electrode again, because the electrode thickness did not undergo significant distortion before and after the cycle.
[0064] The DJ-1 electrode has a complete and continuous three-dimensional conductive structure, which can provide a fast Li+ / e- diffusion channel during the cycle process, while relieving stress and maintaining a complete electrode structure, thus having better electrochemical stability.
[0065] Example 2
[0066] This preferred embodiment 2 provides a method for preparing a three-dimensional structure electrode without a conductive agent and a binder, comprising the following steps:
[0067] S1: 0.01 g of graphene oxide was added to 10 ml of deionized water, and ultrasonic dispersion was performed until the solution was clear; 0.05 g of aluminum silicon alloy powder (silicon weight content was 30%) was added to the obtained clear solution, and the solution was stirred evenly in a water bath at 35° C. for 6 hours, and then filtered and washed with water and anhydrous ethanol respectively (washed with water three times and then washed with ethanol three times), and dried in a vacuum drying oven at 90° C. for 12 hours to obtain product A;
[0068] S2 reacts product A with 0.5M hydrochloric acid in a constant temperature water bath at 28°C for 28 hours, and washes with water and anhydrous ethanol respectively (washes with water three times and then with ethanol three times), and is dried in a vacuum drying oven at 90°C for 12 hours to obtain product B;
[0069] S3: 0.01 g of gelatin and 600 μL of deionized water were stirred at 65 °C to form a uniform solution, which was recorded as solution A.
[0070] S4 Grind 0.02 g of product B and 0.01 g of sodium alginate in a mortar for 30 minutes until the powder particles are uniform, to obtain product C;
[0071] S5: mixing product C with solution A to form a uniform slurry, and coating the slurry on a copper foil (coating thickness is 240 μm) to obtain product D;
[0072] S6: Pour the prepared Cu(NO3)2 solution with a mass concentration of 1% into a nano spray bottle, spray it evenly on the surface of product D (spraying volume is 2 mL), and let it stand at room temperature for 30 minutes to allow it to be completely cross-linked to obtain product E.
[0073] S7 freeze-dried the product E for 48 hours, and then calcined it at 200-600°C for 4 hours at a heating rate of 10°C / min in a tube furnace filled with argon to obtain the three-dimensional structure electrode, which was recorded as DJ-2.
[0074] The SEM image of DJ-2 shows that the electrode surface has a loose and porous structure, and a continuous chain network structure can be clearly observed. DJ-2 has a complete and continuous three-dimensional conductive structure, which can provide fast Li during the cycle. + / e - diffusion channels while relieving stress and maintaining a complete electrode structure, resulting in excellent electrochemical stability.
[0075] Example 3
[0076] This preferred embodiment 3 provides a method for preparing a three-dimensional structure electrode without a conductive agent and a binder, comprising the following steps:
[0077] S1: 0.1 g of graphene oxide was added to 100 ml of deionized water, and ultrasonic dispersion was performed until the solution was clear; 0.2 g of aluminum silicon alloy powder (silicon weight content was 10%) was added to the obtained clear solution, and the mixture was stirred evenly in a water bath at 25° C. for 2 hours, and then filtered and washed with water and anhydrous ethanol respectively (washed with water three times and then washed with ethanol three times), and dried in a vacuum drying oven at 60° C. for 6 hours to obtain product A;
[0078] S2 reacts the product A with 4M hydrochloric acid in a 32°C constant temperature water bath for 12 hours, and washes with water and anhydrous ethanol respectively (washes with water three times and then with ethanol three times), and then dries in a vacuum drying oven at 60°C for 6 hours to obtain product B;
[0079] S3: 0.04 g of gelatin and 1200 μL of deionized water were stirred at 45 °C to form a uniform solution, which was recorded as solution A.
[0080] S4: Grind 0.06 g of product B and 0.04 g of sodium alginate in a mortar for 20 minutes until the powder particles are uniform, to obtain product C;
[0081] S5: mixing product C with solution A to form a uniform slurry, and coating the slurry on a copper foil (coating thickness is 190 μm) to obtain product D;
[0082] S6: Pour the prepared Cu(NO3)2 solution with a mass concentration of 2% into a nano spray bottle, spray it evenly on the surface of product D (spraying volume is 6 mL), and let it stand at room temperature for 10 minutes to allow it to be completely cross-linked to obtain product E.
[0083] S7 freeze-dry the product E for 12 hours, and then calcine it at 200-600° C. for 1-4 hours at a heating rate of 1° C. / min in a tube furnace filled with argon to obtain the three-dimensional structure electrode, which is recorded as DJ-3.
[0084] The SEM image of DJ-3 shows that the surface of the electrode presents a loose and porous structure, and a continuous chain network structure can be clearly observed. DJ-3 has a complete and continuous three-dimensional conductive structure, which can provide fast Li during the cycle process. + / e - diffusion channels while relieving stress and maintaining a complete electrode structure, resulting in excellent electrochemical stability.
[0085] Example 4
[0086] This preferred embodiment 4 provides a method for preparing a three-dimensional structure electrode without a conductive agent and a binder, comprising the following steps:
[0087] S1: 0.03 g of graphene oxide was added to 40 ml of deionized water, and ultrasonic dispersion was performed until the solution was clear; 0.09 g of aluminum silicon alloy powder (silicon weight content was 15%) was added to the obtained clear solution, and the solution was stirred evenly in a water bath at 28° C. for 3 hours, and then filtered and washed with water and anhydrous ethanol respectively (washed with water three times and then washed with ethanol three times), and dried in a vacuum drying oven at 70° C. for 9 hours to obtain product A;
[0088] S2 reacts the product A with 2M hydrochloric acid in a constant temperature water bath at 25°C for 16 hours, and washes with water and anhydrous ethanol respectively (washes with water three times and then with ethanol three times), and then dries in a vacuum drying oven at 70°C for 10 hours to obtain product B;
[0089] S3: 0.02 g of gelatin and 900 μL of deionized water were stirred at 50 °C to form a uniform solution, which was recorded as solution A.
[0090] S4: Grind 0.03 g of product B and 0.02 g of sodium alginate in a mortar for 25 minutes until the powder particles are uniform, to obtain product C;
[0091] S5: mixing product C with solution A to form a uniform slurry, and coating the slurry on a copper foil (coating thickness is 200 μm) to obtain product D;
[0092] S6: Pour the prepared Cu(NO3)2 solution with a mass concentration of 1.5% into a nano spray bottle, spray it evenly on the surface of product D (spraying volume is 3 mL), and let it stand at room temperature for 15 minutes to allow it to be completely cross-linked to obtain product E.
[0093] S7 freeze-dried the product E for 20 hours, and then calcined it at 300°C for 2 hours in a tube furnace filled with argon at a heating rate of 5°C / min to obtain the three-dimensional structure electrode, which was recorded as DJ-4.
[0094] The SEM image of DJ-4 shows that the electrode surface presents a loose and porous structure, and a continuous chain network structure can be clearly observed. DJ-4 has a complete and continuous three-dimensional conductive structure, which can provide fast Li during the cycle process. + / e - diffusion channels while relieving stress and maintaining a complete electrode structure, resulting in excellent electrochemical stability.
[0095] Example 5
[0096] This preferred embodiment 5 provides a method for preparing a three-dimensional structure electrode without a conductive agent and a binder, comprising the following steps:
[0097] S1: 0.08 g of graphene oxide was added to 80 ml of deionized water, and ultrasonic dispersion was performed until the solution was clear; 0.15 g of aluminum silicon alloy powder (silicon weight content was 22%) was added to the obtained clear solution, and the solution was stirred evenly in a water bath at 32° C. for 5 hours, and then filtered and washed with water and anhydrous ethanol respectively (washed with water three times and then washed with ethanol three times), and dried in a vacuum drying oven at 80° C. for 11 hours to obtain product A;
[0098] S2 reacts product A with 3M hydrochloric acid in a 35°C constant temperature water bath for 24 hours, and washes with water and anhydrous ethanol (washes with water three times and then with ethanol three times), and then dries in a vacuum drying oven at 80°C for 10 hours to obtain product B;
[0099] S3: 0.03 g of gelatin and 1100 μL of deionized water were stirred at 60 °C to form a uniform solution, which was recorded as solution A.
[0100] S4: Grind 0.04 g of product B and 0.03 g of sodium alginate in a mortar for 26 minutes until the powder particles are uniform, to obtain product C;
[0101] S5: mixing product C with solution A to form a uniform slurry, and coating the slurry on a copper foil (coating thickness is 200 μm) to obtain product D;
[0102] S6: Pour the prepared Cu(NO3)2 solution with a mass concentration of 1.8% into a nano spray bottle, spray it evenly on the surface of product D (spraying volume is 4 mL), and let it stand at room temperature for 25 minutes to allow it to be completely cross-linked to obtain product E.
[0103] S7 freeze-dried the product E for 40 hours, and then calcined it at 550° C. for 3 hours at a heating rate of 8° C. / min in a tube furnace filled with argon to obtain the three-dimensional structure electrode, which was recorded as DJ-5.
[0104] The SEM image of DJ-5 shows that the electrode surface has a loose and porous structure, and a continuous chain network structure can be clearly observed. DJ-5 has a complete and continuous three-dimensional conductive structure, which can provide fast Li during the cycle. + / e - diffusion channels while relieving stress and maintaining a complete electrode structure, resulting in excellent electrochemical stability.
[0105] Comparative Example 1
[0106] This comparative example 1 provides a method for preparing a three-dimensional structure electrode, comprising the following steps:
[0107] S1: 0.05 g of graphene oxide was added to 50 ml of deionized water, and ultrasonic dispersion was performed until the solution was clear; 0.1 g of aluminum silicon alloy powder (silicon weight content was 20%) was added to the obtained clear solution, and the solution was stirred evenly in a water bath at 30° C. for 5 hours, and then filtered and washed with water and anhydrous ethanol respectively (washed with water three times and then washed with ethanol three times), and dried in a vacuum drying oven at 60-90° C. for 6-12 hours to obtain product A;
[0108] S2 reacts product A with 0.5M hydrochloric acid in a 30°C constant temperature water bath for 24 hours, and washes with water and anhydrous ethanol (washes with water three times and then with ethanol three times), and dries in a vacuum drying oven at 60-90°C for 6-12 hours to obtain product B;
[0109] S3: 0.02 g of gelatin and 0.02 g of sodium alginate were stirred in 1000 μL of deionized water at 55 °C to form a uniform solution, which was recorded as solution A.
[0110] S4: 0.04 g of product B is mixed with solution A to form a uniform slurry, and the slurry is coated on a copper foil (coating thickness is 200 μm) to obtain product c;
[0111] S6: Pour the prepared Cu(NO3)2 solution with a mass concentration of 2% into a nano spray bottle, spray it evenly on the surface of product c (spraying volume is 4 mL), and let it stand at room temperature for 15 minutes to obtain product d.
[0112] S7 freeze-dry the product d for 12-48 hours, and then calcine it at 450°C for 2 hours in a tube furnace filled with argon at a heating rate of 2°C / min to obtain the three-dimensional structure electrode, which is recorded as DB-1.
[0113] In steps S3 and S4, sodium alginate and gelatin are first formed into a mixed solution and then mixed with product B. Since the mixed solution obtained after adding sodium alginate has a high viscosity, it is almost impossible to obtain a uniformly mixed slurry after mixing it with product B. This will directly affect the formation of the product structure in the subsequent coating process. The SEM image of DB-1 also observed that it did not obtain a continuous chain network structure, and its electrochemical stability was poor.
[0114] Comparative Example 2
[0115] This comparative example 2 provides a method for preparing a conventional electrode active material, comprising the following steps:
[0116] S1: 0.05 g of graphene oxide was added to 50 ml of deionized water, and ultrasonic dispersion was performed until the solution was clear; 0.1 g of aluminum silicon alloy powder (silicon weight content was 20%) was added to the obtained clear solution, and the solution was stirred evenly in a water bath at 30° C. for 5 hours, and then filtered and washed with water and anhydrous ethanol respectively (washed with water three times and then washed with ethanol three times), and dried in a vacuum drying oven at 60-90° C. for 6-12 hours to obtain product A;
[0117] Because the surface of the aluminum-silicon alloy microsphere has a positive charge, and the surface of the graphene oxide sheet has a negative charge, the two are electrostatically self-assembled to obtain product A in which graphene oxide is coated on the surface of the aluminum-silicon alloy microsphere;
[0118] S2 reacts product A with 0.5M hydrochloric acid in a 30°C constant temperature water bath for 24 hours, and washes with water and anhydrous ethanol (washes with water three times and then with ethanol three times), and dries in a vacuum drying oven at 60-90°C for 6-12 hours to obtain product B;
[0119] S3: 0.02 g of gelatin and 1000 μL of deionized water were stirred at 55 °C to form a uniform solution, which was recorded as solution A.
[0120] S4: Grind 0.04 g of product B and 0.02 g of sodium alginate in a mortar for 20 minutes until the powder particles are uniform, to obtain product C;
[0121] S5: mixing product C with solution A to form a uniform slurry to obtain product D;
[0122] S6: Product D is mixed with a Cu(NO3)2 solution having a mass concentration of 2%, and after standing at room temperature for 15 minutes, the excess Cu(NO3)2 solution is poured out to obtain Product E.
[0123] S7 freeze-dry the product E for 12-48 hours, and then calcine it at 450° C. for 2 hours at a heating rate of 2° C. / min in a tubular furnace filled with argon to obtain the traditional electrode active material, which is recorded as DB-2.
[0124] Different from Examples 1-5, in step S5 and step S6 of this comparative example, the three-dimensional active electrode structure is not formed directly on the copper foil by spraying, but a conventional blending method is adopted, and then the active material required for the traditional electrode is first prepared by step S7. Although an electrode active material with a three-dimensional cross-linked structure is obtained, this active material DB-2 is not the final traditional electrode. It needs to be further ground in the subsequent preparation process of the traditional electrode, which will cause its three-dimensional structure to be damaged to a certain extent (such as Figure 7 As shown), which leads to a decrease in cycle stability. In addition, additional conductive agents and binders need to be added to the preparation of subsequent traditional electrodes based on Comparative Example 2. Currently, most conductive agents and binders do not have lithium insertion activity, and the conductive agents are usually unevenly distributed during mixing with active materials, which also affects the electrochemical properties of the materials.
[0125] In summary, the present invention uses gelatin and sodium alginate to carry out composite modification of silicon-based materials, and utilizes the cross-linking reaction between sodium alginate and divalent copper ions to directly construct a three-dimensional structure on the copper foil. By directly spraying and high-temperature calcining the coated electrode, a complete and continuous three-dimensional active structure is obtained on the surface of the copper foil, thereby preparing a high-performance three-dimensional structure electrode without a conductive agent and a binder.
[0126] The above are only preferred embodiments of the present invention. It should be understood that the description of the above embodiments is only used to help understand the method and core ideas of the present invention, and is not used to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, etc. made within the ideas and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing a three-dimensional structure electrode without a conductive agent and a binder, characterized in that: The steps include: S1: adding 0.01-0.1g of graphene oxide to 10-100ml of deionized water, and ultrasonically dispersing until the solution is clear; adding 0.05-0.2g of aluminum silicon alloy powder to the obtained clear solution, stirring evenly in a water bath at 25-35°C for 2-6 hours, then filtering and washing with water and anhydrous ethanol respectively, and vacuum drying to obtain product A; S2 uses 0.5-4M hydrochloric acid to react with product A in a constant temperature water bath at 25-35°C for 12-28 hours, and washes with water and anhydrous ethanol for multiple times, and then vacuum-dries to obtain product B; S3: 0.01-0.04 g of gelatin and 600-1200 μL of deionized water were stirred at 45-65° C. to form a uniform solution, which was recorded as solution A. S4 Grind 0.02-0.06 g of product B and 0.01-0.04 g of sodium alginate in a mortar for 20-30 minutes until the powder particles are uniform, to obtain product C; S5: mixing product C with solution A to form a uniform slurry, and coating the slurry on a copper foil to obtain product D; S6: put the prepared Cu(NO3)2 solution into a nano spray bottle, spray it evenly on the surface of product D, and let it stand at room temperature for 10-30 minutes to completely crosslink it to obtain product E; S7 freeze-dries the product E and then calcines it to obtain the three-dimensional structure electrode, which is a porous Si@rGO@N doped with C / Cu single substance.
2. The method for preparing a three-dimensional structure electrode without a conductive agent and a binder according to claim 1, characterized in that: The weight content of silicon in the aluminum-silicon alloy powder in step S1 is 10-30%.
3. The method for preparing a three-dimensional structure electrode without a conductive agent and a binder according to claim 1, characterized in that: The vacuum drying temperature in step S1 and step S2 is 60-90° C., and the drying time is 6-12 hours.
4. The method for preparing a three-dimensional structure electrode without a conductive agent and a binder according to claim 1, characterized in that: The mass concentration of the Cu(NO3)2 solution in step S6 is 1%-2%.
5. The method for preparing a three-dimensional structure electrode without a conductive agent and a binder according to claim 1, characterized in that: The freeze drying time in step S7 is 12-48 hours, and the calcination process conditions are: calcination at 200-600° C. for 1-4 hours at a heating rate of 1-10° C. / min in a tubular furnace filled with argon.
6. The method for preparing a three-dimensional structure electrode without a conductive agent and a binder according to claim 1, characterized in that: In step S5, the sizing agent coating thickness on the aluminum foil is 200 μm.
Citation Information
Patent Citations
Graphene oxide porous composite material and preparation method thereof
CN103480343A
Spherical silicon / carbon composite material for lithium ion battery as well as preparation method and application thereof
CN104868107A